Determinants of income inequality and its effects on economic growth: Evidence from African countries - Matthew O. Odedokun; Jeffery I. Round (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
The paper empirically investigates, in the context of African countries, the determinants of income distribution and inequality, the effect of inequality on economic growth, and the channels through which inequality affects growth. Data for 35 countries over different periods in the last four decades were employed. Factors identified as having affected income distribution include the level of economic development attained, regional factors, size of government budget and the amount of it devoted to subsidies and transfers, phase of economic cycle, share of agricultural sector in total labour force, as well as human and land resources endowment. Some evidence that high inequality reduces growth is also found. The channels through which inequality affect growth are found to be through reduction in secondary and tertiary education investment, reduction in political stability, and increase in fertility rate. There is, however, no evidence that it affects private saving and investment or the size of government expenditure and taxation, contrary to what is contended in the theoretical literature.
Keywords: O1; H5; 330; income distribution; income inequality; economic growth; Einkommensverteilung; Wirtschaftswachstum; Afrika